Clinical Controversies and Research Progress in Lymph Node Dissection for Cervical Cancer - Siqingerile (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Regional lymph node metastasis (LNM) is the main metastatic route of cervical cancer, whose rate of LNM increases in the cancer progression. LNM of cervical cancer is closely related to the cervical cancer staging, treatment method and prognosis. Lymph node dissection (LND) is an important part of standard cervical cancer staging surgeries. In recent years, Sentinel Lymph Node Biopsy (SLNB) has been used in treatments of some tumors, being considered as an alternative to Pelvic Lymph Node Dissection (PLND) in early-stage cervical cancer. However, validation regarding the feasibility of using SLNB alone as an alternative to PLND is still needed. Some scholars support PLND for patients with suspicious lymph nodes detected preoperatively due to reasons such as lower diagnostic sensitivity and specificity of preoperative imaging and potentially better prognosis for surgical staging of advanced stage of cervical cancer. However, recent basic research suggests that lymph nodes are important organs for providing tumor-specific immunity, the preservation of which facilitates immunotherapy. In this way, controversies about whether to use PLND still exist. This paper presents a brief review of the relevant research progress and discusses the new clinical definition and value of lymph nodes in the era of immunotherapy, with a view to providing new directions and ideas for the rational application of LND.